Modificirano numerično modeliranje lomnega vedenja zvarnega spoja v prehodnem področju iz duktilnega h krhkemu lomu - Kozak, Dražan (Kovine zlitine tehnologije, 1998)
Safe use of welded structure depends on fracture mechanics properties of weld joints. These properties are change significantly in the ductile-to-brittle temperature transition region. The aim of this research was to determine an appropriate numerical modelling procedure to define stress-strain conditions at the moment of instability. The modified procedure enables to the fracture behaviour of weld metal at the crack tip in accordance with the theory of fracture mechanics and ensures the verification with experimental results. The use of modified plain stress state at the crack tip during successive increasing of loading enables to obtain acceptable agreement between experimental and numerical results. By FE calculated stress-strain situation at the moment of unstability corresponds to the local condition at the initiation of cleavage fracture on testing specimens. It is possible to use this results on different models for the treshold determination of safe load for real welded structures in the ductile-to-brittle temperature transition region.
Keywords: zvari; zvarni spoji; mehanske lastnosti; preiskava materiala; lom